Analysis of the Queuing System and the Access Bridge of the Kuningan LRT Station - Yogawijaya, Vanogary Eljuvonrodo; Prihartono, Prihartono; Bangkara, B.M.A.S. Anaconda (President University, 2023)
LRT or Light Rail Transit is an alternative to mass transportation from the outskirts to the city center, helping to cut travel time and is integrated with public transportation and activity center locations. LRT effectiveness needs to be supported by LRT stations, the factors included are passenger queues and access bridge. This research delves into an analysis of the queuing system and access bridge at Kuningan LRT station, Jakarta, focusing on the expected waiting time in the system (card tapping time) and the queue at the north and south entrances. The research methodology involved a combination of observation and analytical methods, including data collection on the dimension of the access bridge and LRT station and the use of Queuing theory with multiple single servers' models for data analysis. The research findings reveal that during peak hours, with an estimated daily influx of 10,990 passengers arriving at Kuningan LRT and 10,096 departing from it, the average number of people in the queue is less than one person, with no prolonged queues. The analysis of data presented in this study reveals that the design and construction of the Kuningan LRT access bridge align closely with the pertinent development regulations. The study contributes to the knowledge of queuing systems and provides insights into the number of people estimated to be queuing at the Kuningan LRT station and to forecast how many queues may form during peak hours.